2006
DOI: 10.1002/prs.10136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a silane explosion in a photovoltaic fabrication plant

Abstract: An explosion and fire occurred in a silane gas room in a silicon thin‐film photovoltaic module fabrication plant, resulting in one fatality, and completely destroyed the gas room. The fire also spread outside the room through a polypropylene (PP) exhaust duct to the cleanroom and exhaust scrubbers, resulting in significant damage to the plant. This article investigates the incidents leading up to the explosion, fire escalation, and the incident response. This accident stressed that PP ducts must not be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…In a semi-confined space with gas accumulation, the pop can lead to a gas explosion with significant damage (Ngai et al, 2007). Chang et al (2007) and Chen et al (2006) have reported a destructive silane explosion that is caused by the release and delayed ignition and explosion from a silane cylinder. The incident stressed the importance of understanding the mechanism of delayed ignition from silane release.…”
Section: Introductionmentioning
confidence: 99%
“…In a semi-confined space with gas accumulation, the pop can lead to a gas explosion with significant damage (Ngai et al, 2007). Chang et al (2007) and Chen et al (2006) have reported a destructive silane explosion that is caused by the release and delayed ignition and explosion from a silane cylinder. The incident stressed the importance of understanding the mechanism of delayed ignition from silane release.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2006), Chang et al (2007) and Peng et al (2008). The cause of leak is a failed silane cylinder valve with loosened valve stem retainer.…”
Section: Incidents and Emergency Response 41 Silanementioning
confidence: 99%
“…A TNT equivalency model using a yield factor of 1 and accounting for one reflecting surface was used to fit the overpressure data. Ngai et al (2007) performed release and explosion tests from cylinder and gas cabinet following the tragic silane explosion incident in 2005 (Chen et al, 2006;Chang et al, 2007). In these particular experiments, it was demonstrated that ignition was triggered by flow shutoff at the outlet rather than by autoignition of metastable silane/air mixture in the gas cloud.…”
Section: Introductionmentioning
confidence: 96%